African presidential republics - Blondel, Jean. (New York Routledge, 2019)
This book provides a systematic assessment of the behaviour of some relatively successful presidents in African presidential republics, examining the part played by presidents in the development of their countries.
Includes index
Keywords: Presidents--Africa.